Impact of one loop corrections on light neutrino masses in the low scale susy seesaw - Suarez Navarro, Omar Giancarlo (2023)
This thesis covers the study of one-loop quantum corrections to the light neutrino masses. In the first part, we examine the extension of the standard model with right-handed neutrinos, where the Seesaw type I is present, allowing accessible masses for experimental searches. However, considering the corrections to the light neutrinos masses requires the pairs of heavy neutrinos to appear as pseudo Dirac particles, implying a suppression of the LNV parameters. In the second part, the supersymmetric contributions are analyzed in order to relax the lepton number violation (LNV) restrictions and achieve a greater difference between the heavy neutrino masses, as well as large mixings. When analyzing the destructive interference between the supersymmetric (which we describe as reducible and irreducible) and non-supersymmetric contributions, we found parameter regions where cancellations occur, however they are very small. So, the addition of SUSY does not guarantee the effect called screening, and the cases that are favorable need some degree of fine-tuning. In all cases, the numerical results of the analytical one-loop expressions calculated in the νRSM and νRMSSM models are checked with SPheno.